Casualty Behaviour and Mass Decontamination: A Narrative Literature Review - Francis Long; Arnab Majumdar (Urban Science, 2025)
Chemical, biological, radiological, and nuclear (CBRN) incidents pose significant challenges requiring swift, coordinated responses to safeguard public health. This is especially the case in densely populated urban areas, where the public is not only at risk but can also be of assistance. Public cooperation is critical to the success of mass decontamination efforts, yet prior research has primarily focused on technical and procedural aspects, neglecting the psychological and social factors driving casualty behaviour. This paper addresses this gap through a narrative literature review, chosen for its flexibility in synthesising fragmented and interdisciplinary research across psychology, sociology, and emergency management. The review identified two primary pathways influencing casualty decision making: rational and affective. Rational pathways rely on deliberate decisions supported by clear communication and trust in responders’ competence, while affective pathways are shaped by emotional responses like fear and anxiety, exacerbated by uncertainty. Trust emerged as a critical factor, with effective —i.e., transparent, empathetic, and culturally sensitive— communication being proven to enhance public cooperation. Cultural and societal norms further shape individual and group responses during emergencies. This paper demonstrates the value of narrative reviews in addressing a complex, multifaceted topic such as casualty behaviour, enabling the integration of diverse insights. By emphasising behavioural, psychological, and social dimensions, the results of this paper offer actionable strategies for emergency responders to enhance public cooperation and improve outcomes during CBRN incidents.